Threshold electron-positron pair production by a polarized electron in a strong magnetic field - Novak, O.P.; Kholodov, R.I. (Вопросы атомной науки и техники, 2012)
Resonant e⁺e⁻–-pair production by an electron in a magnetic field near the process threshold is analytically studied. Using the Nikishov's theorem we estimate the number of events in the magnetic field equivalent to laser wave in the SLAC experiment. The obtained estimate is in reasonable agreement with the experimental data. Аналитически исследовано образование e⁺e⁻–-пары электроном в магнитном поле вблизи порога процесса. Произведена оценка числа событий в эксперименте SLAC с использованием теоремы Никишова. Полученное число событий согласуется с экспериментальными данными. Аналітично досліджено утворення e⁺e⁻–-пари електроном в магнітному полі поблизу порогу процесу. Одержана оцінка числа подій в експерименті SLAC з використанням теореми Нікішова. Знайдене число подій узгоджується з експериментальними даними.